Pengalaman Orang Tua Sebagai Prediktor Pengetahuan, Sikap, Self Efficacy Orang Tua Dalam Edukasi Pencegahan Kekerasan Seksual Pada Anak - Crisdiansyah; Linda Suwarni; Selviana; Vidyastuti; Helfi Nolia (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Background: Parental education is important in preventing sexual violence against children. Parents need good knowledge, attitudes, and self-efficacy to educate their children, though their effectiveness is affected by various factors. Objective: This study aimed to predict the knowledge, attitudes, and self-efficacy of parents in education to prevent sexual violence in children. Methods: A quantitative design with a cross-sectional approach was used. The sample is 400 parents who have children aged 12-17 years. Data was collected through direct interviews and analyzed using univariate and bivariate (Chi-Square test with 95% CI). Results: the experience of parents receiving education on preventing sexual violence against children correlate with knowledge (p-value = 0.012), attitude (p-value = 0.0000) and self-efficacy (p-value = 0.000). Conclusion: The experience of parents helps predict knowledge, attitudes, and self-efficacy in providing education to prevent sexual violence against children.)